Asthma education: Five key messages. Issue 4 (July 2016) - Evans-Agnew, Robin; Cooper, Cindy
Abstract : Teaching your patients about asthma is important for reducing disparities, but it's complicated and your time is limited. We help you simplify the information and provide tips on how to use cultural humility when working with children and families.